46 Effects of Packaging Conditions on Volatile Compounds of Raw Beef from Two Muscles. (1st March 2018) - Cramer, T; Legako, J F; Ponce, J A; Brooks, J C
Abstract: The objective of this study was to determine the impact of packaging conditions on volatile compounds of raw steaks from two muscles. Strip loin and sirloin subprimals were collected from ten USDA Low Choice carcasses. Longissimus dorsi (LD) and gluteus medius (GM) steaks were cut at 14d postmortem and allotted to packaging conditions: traditional vacuum packaging (VAC), rollstock (ROLL), carbon monoxide modified atmosphere lidded trays (0.4%CO/30%CO2 /69.6%N2, CO), high-oxygen modified atmosphere lidded trays (80%O2 /20%CO2, HIOX), and traditional overwrap (OW). Samples were then stored in darkness for 7 additional d, then ROLL, CO, HIOX and OW were displayed for 48 h under 1900 lux of continuous fluorescent lighting. After display volatile compounds were measured from raw steaks to evaluate impacts of packaging conditions. Packaging × muscle interactions were observed wherein HIOX-LD had greater concentrations of pentane and isobutyraldehyde ( P ≤ 0.013) compared with other packaging × muscle treatments. Greater concentrations of 2-methylbutanal were observed in HIOX-LD and OW-LD ( P = 0.01) compared with GM muscle or other packaging types. These findings may indicate high oxygen in the packaging system promotes greater oxidation of LD as compared with GM; however, HIOX-GM had the greatest concentration of heptanal ( P = 0.03). A packaging effect was observed for 25 volatile compounds originating from lipid degradation ( P ≤ 0.04). A clear separation was evident based on oxygen exposure; HIOX packaging showed elevated ( P < 0.05) lipid oxidation products compared with ROLL, VAC, OW or CO packaging, including three aldehydes (nonanal, pentanal, hexanal), three methyl esters (nonanoic acid methyl ester, hexanoic acid methyl ester, heptanoic acid methyl ester); three alkanes (tetradecane, octane, nonane); three alcohols (1-octen-3-ol, 1-octanol, 2-phenylisopropanol), 2, 3-pentanedione, 2-heptanone, butyrolactone, and hexanoic acid. Treatments inhibiting oxygen exposure (ROLL, VAC) showed increased alkenes (2-methyl-1-pentene, 1-octene, 2, 4-dimethyl-1-heptene, toluene), carbon disulfide, 3-methylbutanal, butanoic acid methyl ester, and 4-methylheptane compared with HIOX. Muscle type influenced 15 volatile compounds. The GM had greater concentrations of 11 volatiles (P ≤ 0.0022), including two ketones (2-propanone, 2, 3-butanedione) and three methyl esters (hexanoic acid methyl ester, heptanoic acid methyl ester, octanoic acid methyl ester). Raw LD exhibited greater concentrations of ethanol ( P = 0.0002), 2-methyl-1-pentene ( P = 0.05), methylpropionate ( P = 0.0007) and butyrolactone ( P = 0.03). These findings suggest packaging conditions greatly influence concentrations of volatile compounds derived from lipid oxidation. Muscle was less influential; however, observed muscle differences may have implications for the well-established variation in flavor and aroma between beef muscles.